Karakter Ketekunan dan Keterampilan Proses Matematika: Pengaruh Pembelajaran Matematika Kelas Tinggi di Sekolah Dasar Pada Materi Operasi Hitung - Noor Fajriah; Kamid (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the effect of the persistence character on the mathematical processing skills of high school students in arithmetic operations. Then, find out the differences in student learning persistence and elementary school math processing skills. This research method uses a mixed practice with an explanatory design. The research sample was grouped into three schools, namely elementary school Basirih 5 from South Kalimantan, elementary school 64 Muara Bulian, and elementary school 131 Muara Bulian from Jambi province, which we will use with a total sample of 60 students—sampling using a simple random sampling technique. The results of data analysis using the independent sample t-test obtained a value of sig <0.05, so it can be said that the character of the persistence of students in each elementary school is different, and for the mathematical processing skills variable sig is <0.05 so that the KPM for each school is different. The results of a simple linear regression test obtained a sig value of 0.025 in the high class of elementary school Basirih 5, elementary school 64, and elementary school 131 Muara Bulian received a sig value of 0.030, where the sig value <0.05, which means that the persistence of character affects the students' mathematical process skills. The conclusion of this study is that learning persistence is an important factor affecting students' mathematical process skills, with the implication that strengthening the character of perseverance can improve mathematical learning outcomes.